2014
DOI: 10.4028/www.scientific.net/amm.543-547.4428
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing, Organizational Learning and Competitive Advantage to Supply Chain Management

Abstract: We introduce a model to examine factors influencing Competitive Advantage and implementation in inter-firm. The model comprises nine research hypotheses with nine constructs, including Innovation Knowledge, Technology Creation, Quality Management, Resource, Communication, Opportunistic Behavior, Organizational Learning, Information Sharing and Competitive Advantage. The constructs are measured by well-supported measures in the literature. The hypotheses are tested via an empirical study of supply chains. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The results of this study showed that knowledge sharing has a positive and meaningful effect on gaining competitive advantage. This finding is consistent with the research results of Meihami and Meihami (2014), Hana (2013), Huang et al (2014) and Mundra et al (2011). Grant (1996) claimed that knowledge is regarded as a chief source of competitive advantage because it provides intangible assets that are unique, inimitable and incomparable.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that knowledge sharing has a positive and meaningful effect on gaining competitive advantage. This finding is consistent with the research results of Meihami and Meihami (2014), Hana (2013), Huang et al (2014) and Mundra et al (2011). Grant (1996) claimed that knowledge is regarded as a chief source of competitive advantage because it provides intangible assets that are unique, inimitable and incomparable.…”
Section: Discussionsupporting
confidence: 93%